Blockchain and Corporate Criminal Liability: Law Reform and the Technological Revolution in Corporate Accountability - Herlina Manullang; Zico Junius Fernando; Asrul Ibrahim Nur (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
The rapid development of blockchain technology is reshaping various dimensions of governance, particularly in strengthening corporate accountability and addressing corporate criminal liability. This paper examines how blockchain, through its inherent features of decentralization, transparency, immutability, and smart contracts, can offer innovative tools to reform legal frameworks governing corporate behavior. These features enable more robust compliance monitoring, secure and tamper-proof evidence handling, and efficient fraud detection mechanisms. By integrating blockchain into corporate governance systems, companies can enhance regulatory compliance and reduce the risks of misconduct. Smart contracts, in particular, allow the automation of enforcement procedures, minimizing human error and corruption while increasing legal predictability. This paper further explores how blockchain facilitates proactive legal oversight and redefines how liability is tracked and enforced within corporate structures. Despite its potential, the adoption of blockchain within legal systems faces several challenges, including regulatory ambiguity, privacy issues, and the necessity for international legal harmonization. To illustrate the real-world application of blockchain in legal reforms, this study presents comparative case analyses from jurisdictions that are at the forefront of blockchain regulation and implementation in corporate governance. Ultimately, this paper argues that blockchain serves not merely as a technological tool but as a catalyst for transforming the philosophy and practice of corporate criminal liability. To realize its full potential, collaborative efforts among legislators, regulators, and private sector actors are essential. The paper concludes with strategic recommendations for incorporating blockchain into corporate criminal law, aiming to enhance transparency, ensure compliance, and strengthen governance frameworks in line with technological progress.